2020
DOI: 10.1038/s41598-020-69297-0
|View full text |Cite
|
Sign up to set email alerts
|

Plasma extracellular vesicle proteins are associated with stress-induced myocardial ischemia in women presenting with chest pain

Abstract: Diagnosing stable ischemic heart disease (IHD) is challenging, especially in females. Currently, no blood test is available. Plasma extracellular vesicles (EV) are emerging as potential biomarker source. We therefore aimed to identify stress induced ischemia due to stable IHD with plasma extracellular vesicle protein levels in chest pain patients. We analyzed 450 patients suspected for stable IHD who were referred for 82 Rb PET/CT in the outpatient clinic. Blood samples were collected before PET/CT and plasma … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 18 publications
(26 citation statements)
references
References 46 publications
0
26
0
Order By: Relevance
“…Iodixanol density gradient centrifugation of the subfraction was used to determine in which density fraction NLRP3 protein was present in the TEX fraction. Characterization of the density fractions of TEX isolation was described in detail before [21,22]. In these previous studies, we show that with the precipitation method we used, after density gradient centrifugation there was CD9 positivity (Western blot) in the 1,05-1,09 density.…”
Section: Characterization Of Extracellular Vesiclesmentioning
confidence: 68%
See 1 more Smart Citation
“…Iodixanol density gradient centrifugation of the subfraction was used to determine in which density fraction NLRP3 protein was present in the TEX fraction. Characterization of the density fractions of TEX isolation was described in detail before [21,22]. In these previous studies, we show that with the precipitation method we used, after density gradient centrifugation there was CD9 positivity (Western blot) in the 1,05-1,09 density.…”
Section: Characterization Of Extracellular Vesiclesmentioning
confidence: 68%
“…Serum EV or cell culture medium EV subfractions were isolated using a standardized protocol [21,22].…”
Section: Isolation Of Extracellular Subfractionsmentioning
confidence: 99%
“…The myomarker study cohort consisted of consecutive patients presenting with stable chest pain at the outpatient clinic of the Meander Medical Centre in the Netherlands. Details on the study design and study population can be found in a previous publication [108]. For this study, a case control analysis of 44 men suspected of CCS was performed.…”
Section: Extracellular Vesicle Contentmentioning
confidence: 99%
“…For EV-based diagnosis of CCS, not many data exist. A recent study investigated whether a selected group of EV-proteins were associated with CCS [108]. EV-Serpin C1, EV-CD14, EV-Serpin G1, EV-Serpin F2 and EV-Cystatin C (mostly in the HDL-subpopulation) were shown to be independently associated with the presence of stress-induced ischemia.…”
Section: Extracellular Vesicle Contentmentioning
confidence: 99%
See 1 more Smart Citation